2018
DOI: 10.1016/j.ajog.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity for primary dysmenorrhea: a systematic review and meta-analysis of randomized controlled trials

Abstract: Clinicians can inform women that physical activity may be an effective treatment for primary dysmenorrhea but there is a need for high-quality trials before this can be confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 49 publications
(82 reference statements)
4
65
1
7
Order By: Relevance
“…In the last decade, several authors have noted the need to further study both the pharmacological and non-pharmacological management of menstrual pain [ 10 , 11 , 35 ], especially considering that 18% of non-steroidal anti-inflammatory treatments are ineffective for dysmenorrhea, the primary treatment for this condition [ 36 ]. There is increasing evidence of the efficacy of non-pharmacological methods for dysmenorrhea, such as aerobic exercise, yoga, taping and transcutaneous electrical nerve stimulation [ 20 , 21 , 37 , 38 , 39 ]. Furthermore, a study conducted in the USA among women suffering from dysmenorrhea identified the reasons why women did not seek medical advice: they believed professionals would be unable to help, they distrusted the available treatments and felt ashamed or fearful of seeking help for this problem [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, several authors have noted the need to further study both the pharmacological and non-pharmacological management of menstrual pain [ 10 , 11 , 35 ], especially considering that 18% of non-steroidal anti-inflammatory treatments are ineffective for dysmenorrhea, the primary treatment for this condition [ 36 ]. There is increasing evidence of the efficacy of non-pharmacological methods for dysmenorrhea, such as aerobic exercise, yoga, taping and transcutaneous electrical nerve stimulation [ 20 , 21 , 37 , 38 , 39 ]. Furthermore, a study conducted in the USA among women suffering from dysmenorrhea identified the reasons why women did not seek medical advice: they believed professionals would be unable to help, they distrusted the available treatments and felt ashamed or fearful of seeking help for this problem [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms related with dysmenorrhea were measured based on Andersch-Milsom Verbal Multidimensional Scoring System. Four grades have been mentioned in this scale for the severity of dysmenorrhea symptoms as follows: score 0 (no symptoms); score 1 (mild symptoms are present but do not interfere with daily activities); score 2 (symptoms exist and interfere with daily tasks but are moderate and not debilitating; score 3 (symptoms are quite debilitating and severe (15).…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…Prostaglandins can cause severe uterine contractions, fatigue, dizziness, headache, nervous change and other related symptoms (5)(6)(7). There are several treatments for primary dysmenorrhea and associated symptoms, including contraceptive pills (8,9), vitamin E compounds (10), vitamin D (10)(11)(12), sh oil supplements (13), diet (14), exercise and physical activity (15), acupuncture (16), topical heat (17), psychotherapy (18) and Nonsteroidal anti-in ammatory drugs (NSAIDs).…”
Section: Introductionmentioning
confidence: 99%
“…Primary dysmenorrhea is a gynecological problem which generally occurs to young women and adolescents with no pelvic abnormalities but complaints of cramping pain in the lower abdomen, spreading to the lower back and accompanied by complaint of headache, nausea, fatigue, vomiting, irritability, diarrhea and uncomfortable feeling [1][2][3] . Pain usually goes with menstrual bleeding and last from 48 to 72 hours 4 .…”
Section: Introductionmentioning
confidence: 99%